2019
DOI: 10.1021/acs.jpclett.9b03480
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Relaxation Dynamics of a Semiconductor Copper(I) Thiocyanate (CuSCN) Film as a Hole-Transporting Layer

Abstract: The semiconductor CuSCN film, which is typically used as the hole-transporting layer (HTL) in solar cell studies, has been investigated by Fourier transform infrared (FTIR) spectroscopy and ultrafast transient infrared (IR) spectroscopy. A sharp peak at 2175 cm −1 corresponding to the CN vibrational stretching mode in CuSCN was observed, and the peak frequency remained unchanged by varying the thickness of the CuSCN thin film. Vibrational relaxation measurements showed that the 0−1 and 1−2 transitions of CN st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The specific interaction between the cations and the crown ethers can be understood from the viewpoint of the vibrational relaxation dynamics of the SCN – anions. As previous studies demonstrated, the vibrational population decay of the SCN – probe is sensitive to the local environments in the condensed phases. ,, Also, the orientational dynamics of the SCN – would be expected to be different, which would provide a further molecular-level understanding of the specific host–guest interactions in the complexes of crown ethers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The specific interaction between the cations and the crown ethers can be understood from the viewpoint of the vibrational relaxation dynamics of the SCN – anions. As previous studies demonstrated, the vibrational population decay of the SCN – probe is sensitive to the local environments in the condensed phases. ,, Also, the orientational dynamics of the SCN – would be expected to be different, which would provide a further molecular-level understanding of the specific host–guest interactions in the complexes of crown ethers.…”
Section: Resultsmentioning
confidence: 97%
“…The ultrafast IR spectroscopy setup has been described in our previous studies. Here, we only give the simplest description. The ultrafast IR spectroscopic measurement was based on the pump–probe scheme.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…The ultrafast 2D IR spectroscopy experimental setup had been described in our previous reports. , The scheme of the 2D IR spectroscopy was realized by using the pump–probe design. A picosecond (ps) amplifier (Spectra Physics) with output frequency at 800 nm and a femtosecond (fs) amplifier (Spectra Physics) with output frequency at 800 nm were independently operated and synchronized with the same seed pulse generated from a 78 MHz Ti-sapphire oscillator (Spectra Physics).…”
Section: Methodsmentioning
confidence: 99%
“…The nature of primary photo-excitations in organic semiconductors, particularly in conjugated polymers, has been the subject of an active debate in the scientific community for more than 3 decades [176][177][178][179]. The mechanisms underlying photogeneration of charge carriers as well as thermalization promptly after photoexcitation are indicative of the strength of electron-electron interactions relative to the bandwidth (as manifested by the exciton binding energy), while carriers transport, trapping, and recombination processes are intimately related to the degree of order, purity, and morphology of the materials.…”
Section: Organic Semiconductorsmentioning
confidence: 99%